IoT and communication in Malaysia: new frontiers - Abu Bakar, Muhammad Nabihan; Yahya, Masliya (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
The Internet of Things (IoT) has transformed communication globally and in Malaysia by enabling interconnected devices, sensors, and software to exchange data in real time, shifting communication from traditional linear models to dynamic human-to-human, human-to-machine, and machine-to-machine interactions. Recognizing its potential, Malaysia introduced the National IoT Strategic Roadmap in 2015 to strengthen IoT integration in smart city development, support modern infrastructure, and drive economic growth.